See You at the Crossroads: Hip Hop Scholarship at the Intersections
XVI, 198 p.
Keywords: See You at the Crossroads: Hip Hop Scholarship at the Intersections Dialectical Harmony, Ethics, Aesthetics, and Panoply of Voices offers several essential contributions to the field of Hip Hop studies. It presents several snapshots of innovative work within (and at the intersections between) several intellectual fields of study. The collection of essays reveal the dialectical harmony and solidarity with which Hip Hop scholars, activists, and artists collectively mobilize, stand together, and collaboratively sustain in hopes of realizing social justice and actualizing global liberation. Several leading scholars in Hip Hop studies also provide insight to the aesthetic, the affordances, the ethics, and panoply of voices in Hip Hop culture. Finally, through empirical research, direct artistic engagement and critical pedagogical praxis, the contributors demonstrate how Hip Hop Based Education (HHBE) catalyzes civic engagement and democratic participation in schools through the use of democratic aesthetic tools to galvanize social change.